The nutmeg's curse : parables for a planet in crisis - Ghosh, Amitav, 1956- (The University of Chicago Press, 2021)
"The Nutmeg's Curse: Parables for a Planet in Crisis frames climate change and the Anthropocene as the culmination of a history that begins with the discovery of the New World and of the sea route to the Indian Ocean. Ghosh makes the case that the political dynamics of climate change today are rooted in the centuries-old geopolitical order that was constructed by Western colonialism. This argument is set within a broader narrative about human entanglements with botanical matter-spices, tea, sugarcane, opium, and fossil fuels-and the continuities that bind human history with these earthly materials. Ghosh also writes explicitly against the backdrop of the COVID-19 pandemic, the Black Lives Matter protests, and international immigration debates, among other pressing issues, framing these ongoing crises in a new way by showing how the colonialist extractive mindset is directly connected to the deep inequality we see around us today"--